Supporting urban development in Latvian large cities through integrated territorial investments - Enģelis, Kārlis (Riga Graduate School of Law, 2017)
The regulatory framework of the EU Structural and Investment Funds (ESI Funds) has a strong territorial dimension and support to designated territories, particularly municipalities, is common. Provision of support to territories is an issue of common interest and the European Commission addresses it in the ESI Funds programming phase from different aspects one being the use of integrated approaches to tackle territorial challenges at sub-national and sub-regional levels. In the 2014-2020 programming period the territorial dimension has been further strengthened by a conditionality that beneficiary countries have to allocate 5% of their respective European Regional Development Fund (ERDF) envelope to sustainable urban development. This can be facilitated using three options – through a dedicated operational program, through a dedicated priority axis or by making Integrated Territorial Investment (ITI). The latter is a new tool introduced in the Regulation (EU) No 1303/20131 (ERDF Regulation) and the Common Strategic Framework2, a delivery mechanism which is included in the regulatory acts for ESI Funds. The ITI tool is voluntary and a Member State may opt not to use it giving preference to other forms of fund management.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Investment law